The Role of Public Relations in Educational Development in Higher Education Institutions - Afriani, Linda; Timan, Agus (IJESS International Journal of Education and Social Science, 2024)
This study aims to examine the strategic role of public relations (PR) in supporting the development of higher education institutions. By adopting McLean's (2006) organizational development model, this study analyzes how PR practices can be integrated into each stage of organizational development, from planning to evaluation. The research findings indicate that PR plays a crucial role in building a positive institutional image, facilitating effective communication with various stakeholders, and supporting the implementation of organizational strategies. Through a literature review, this study identifies that PR is actively involved in every stage of organizational development, such as building initial agreements, communicating development plans, conducting organizational culture analysis, designing communication strategies, and evaluating the impact of interventions. This study concludes that the integration of PR practices and the organizational development process is key to enhancing the competitiveness of higher education institutions. By optimizing the role of PR, institutions can achieve their strategic goals, build stronger relationships with stakeholders, and enhance their reputation in the eyes of the public.